Google-Based Learning and Learning Motivation: The Impact and Interaction on Students’ Mathematical Communication - Rahmawati, Nurina Kurniasari; Kusuma, Arie Purwa; Widyawati, Santi; Putra, Fredi Ganda (Universitas Islam Negeri Raden Intan Lampung, 2020)
Poor mathematical communication skills and motivation are influenced by several factors, such as the use of learning models used by teachers in learning. The use of appropriate learning models can improve students’ mathematical communication skills and motivation. This study aimed to determine the effect of the discussion learning model using Google Classroom and Google Form on students' mathematical communication in terms of students’ learning motivation. This type of research is quasi-experimental. Data were analyzed using two-way analysis of variance with unequal cells. Based on the results, it can be concluded that the discussion learning model using Google Classroom provided better communication skills than the learning model using Google Form, (2) there was no difference in the effect of learning motivation on students' mathematical communication, and (3) there was no interaction between learning model and learning motivation towards students' mathematical communication skills. Further research is needed to develop learning models using Google Classroom and Google Form by taking into account the characteristics of other students that are adjusted to the school curriculum.